Variation in estimates of the footprint of large, ground-mounted photovoltaic solar energy in the United States and its associated land-cover change across three datasets - Michael O. Levin; Emma Forester; Elizabeth L. Kalies; Lauren Goodman; Jason S. Hagani; Chevon C. Holmes; Noah Z. Krasner; Caitlin Markus; Jared B. Meek; Anubhav Vanamamalai; Shivani Agarwal; Uzma Ashraf; et al. (Journal of Environmental Management, 2025)

Rankings of tuberculosis antibiotic treatment regimens are sensitive to spatial scale, detection limit, and initial host bacterial burden - Christian T. Michael; Maral Budak; Pauline Maiello; Kara Kracinovsky; Mark Rodgers; Jaime Tomko; Philana Ling Lin; JoAnne Flynn; Jennifer J. Linderman; Denise Kirschner (Journal of Theoretical Biology, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Sensitivity of AERMOD (V21112) RLINEXT dispersion model outputs by source type to variability in single noise barrier height and separation distance - Hongyu Lu; Daejin Kim; Haobing Liu; Tian Xia; William Reichard; Michael O. Rodgers; Randall Guensler (Atmospheric Pollution Research, 2024)

Issues in the inhalation toxicity testing and hazard assessment for low density particulate materials such as synthetic amorphous silica (SAS) - Wolfgang Dekant; Evangelia E. Antoniou; Axel Bosch; Gustav Gerd Bruer; Thomas Colnot; Otto Creutzenberg; Claus-Peter Drexel; Rodger Duffin; Nils Krueger; Jürgen Nolde; Craig Poland; Dirk Schaudien; et al. (Toxicology Letters, 2024)

Bearing capacity of shallow foundations on Florida limestone: A study of single layer and rock-over-sand subsurface - Kunyu Yang; Michael McVay; Thai Nguyen; Kaiqi Wang; Xiaoyu Song; Scott Wasman; Michael Rodgers; David Horhota; Rodrigo Herrera (Computers and Geotechnics, 2023)

Corrigendum to “Issues in the inhalation toxicity testing and hazard assessment for low density particulate materials such as synthetic amorphous silica (SAS)” [Toxicol. Lett. (in press)] - Wolfgang Dekant; Evangelia E. Antoniou; Axel Bosch; Gustav Gerd Bruer; Thomas Colnot; Otto Creutzenberg; Claus-Peter Drexel; Rodger Duffin; Nils Krueger; Jürgen Nolde; Craig Poland; Dirk Schaudien; et al. (Toxicology Letters, 2023)

An Experimental Platform to Study Wind, Hydrodynamic, and Biochemical Conditions in the Littoral Zone During Extreme Coastal Storms - Brian Phillips; Forrest Masters; Britt Raubenheimer; Maitane Olabarrieta; Elise Morrison; Pedro Fernández-Cabán; Christopher Ferraro; Justin Davis; Taylor Rawlinson; Michael Rodgers (Oceanography, 2023)
Tropical cyclones and other extreme coastal storms cause widespread interruption and damage to meteorological and hydrological measurement stations exactly when researchers need them most. There is a longstanding need to collect collocated and synchronized measurements in areas where storms severely damage civil/coastal infrastructure. To fill this observational gap, researchers led by author Masters developed a state-of-the-art monitoring station called a “Sentinel.” Sentinels are intended for temporary installation on the beach between the mean tidal datum and the sand dunes and are engineered to operate in and measure extreme wind, storm surge, wave, and hazardous water quality conditions. They are envisioned as a shared-use resource—a hardened IoT (Internet of Things) platform set up in the right place at the right time to study wind and wave loads, coastal erosion and morphology changes, water quality, and other processes during extreme coastal storms.

Seismic surveys near gray whale feeding areas off Sakhalin Island, Russia: assessing impact and mitigation effectiveness - Lisanne Aerts; Michael R. Jenkerson; Vladimir E. Nechayuk; Glenn Gailey; Roberto Racca; Arny L. Blanchard; Lisa K. Schwarz; H. Rodger Melton (Environmental Monitoring and Assessment, 2022)
In 2015, two oil and gas companies conducted seismic surveys along the northeast coast of Sakhalin Island, Russia, near western gray whale ( Eschrichtius robustus ) feeding areas. This population of whales was listed as Critically Endangered at the time of the operations described here but has been reclassified as Endangered since 2018. The number and duration of the 2015 seismic surveys surpassed the level of previous seismic survey activity in this area, elevating concerns regarding disturbance of feeding gray whales and the potential for auditory injury. Exxon Neftegas Limited (ENL) developed a mitigation approach to address these concerns and, more importantly, implemented a comprehensive data collection strategy to assess the effectiveness of this approach. The mitigation approach prioritized completion of the seismic surveys closest to the nearshore feeding area as early in the season as possible, when fewer gray whales would be present. This was accomplished by increasing operational efficiency through the use of multiple seismic vessels and by establishing zones with specific seasonal criteria determining when air gun shutdowns would be implemented. These zones and seasonal criteria were based on pre-season modeled acoustic footprints of the air gun array and on gray whale distribution data collected over the previous 10 years. Real-time acoustic and whale sighting data were instrumental in the implementation of air gun shutdowns. The mitigation effectiveness of these shutdowns was assessed through analyzing short-term behavioral responses and shifts in gray whale distribution due to sound exposure. The overall mitigation strategy of an early survey completion was assessed through bioenergetics models that predict how reduced foraging activity might affect gray whale reproduction and maternal survival. This assessment relied on a total of 17 shore-based and 5 vessel-based teams collecting behavior, distribution, photo-identification, prey, and acoustic data. This paper describes the mitigation approach, the implementation of mitigation measures using real-time acoustic and gray whale location data, and the strategy to assess impacts and mitigation effectiveness.

Translating a Global Emission-Reduction Framework for Subnational Climate Action: A Case Study from the State of Georgia - Marilyn A. Brown; Blair Beasley; Fikret Atalay; Kim M. Cobb; Puneet Dwiveldi; Jeffrey Hubbs; David M. Iwaniek; Sudhagar Mani; Daniel Matisoff; Jaqueline E. Mohan; Jeffrey Mullen; Michael Oxman; et al. (Environmental Management, 2021)
Subnational entities are recognizing the need to systematically examine options for reducing their carbon footprints. However, few robust and comprehensive analyses are available that lay out how US states and regions can most effectively contribute. This paper describes an approach developed for Georgia—a state in the southeastern United States called “Drawdown Georgia”, our research involves (1) understanding Georgia’s baseline carbon footprint and trends, (2) identifying the universe of Georgia-specific carbon-reduction solutions that could be impactful by 2030, (3) estimating the greenhouse gas reduction potential of these high-impact 2030 solutions for Georgia, and (4) estimating associated costs and benefits while also considering how the solutions might impact societal priorities, such as economic development opportunities, public health, environmental benefits, and equity. We began by examining the global solutions identified by Project Drawdown. The resulting 20 high-impact 2030 solutions provide a strategy for reducing Georgia’s carbon footprint in the next decade using market-ready technologies and practices and including negative emission solutions. This paper describes our systematic and replicable process and ends with a discussion of its strengths, weaknesses, and planned future research.

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

Social-ecological change in the Omo-Turkana basin: A synthesis of current developments - Jennifer Hodbod; Edward G. J. Stevenson; Gregory Akall; Thomas Akuja; Ikal Angelei; Elias Alemu Bedasso; Lucie Buffavand; Samuel Derbyshire; Immo Eulenberger; Natasha Gownaris; Benedikt Kamski; Abdikadir Kurewa; et al. (Ambio, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Corynebacterium diphtheriae HmuT: dissecting the roles of conserved residues in heme pocket stabilization - Elizabeth B. Draganova; Seth A. Adrian; Gudrun S. Lukat-Rodgers; Cyrianne S. Keutcha; Michael P. Schmitt; Kenton R. Rodgers; Dabney W. Dixon (JBIC Journal of Biological Inorganic Chemistry, 2016)

Long-Period Ground Motion in the Arabian Gulf from Earthquakes in the Zagros Mountains Thrust Belt - Arben Pitarka; Abdullah Al-Amri; Michael E. Pasyanos; Arthur J. Rodgers; Robert J. Mellors (Pure and Applied Geophysics, 2015)

Nutrient and heavy metals in decaying harvest residue needles on drained blanket peat forests - Zaki-ul-Zaman Asam; Mika Nieminen; Annu Kaila; Raija Laiho; Sakari Sarkkola; Mark O’Connor; Connie O’Driscoll; Afshan Sana; Michael Rodgers; Xinmin Zhan; Liwen Xiao (European Journal of Forest Research, 2014)

Spatial and seasonal variation of peatland-fed riverine macroinvertebrate and benthic diatom assemblages and implications for assessment: a case study from Ireland - Connie O’Driscoll; Elvira de Eyto; Michael Rodgers; Mark O’Connor; Zaki-ul-Zaman Asam; Martyn Kelly; Liwen Xiao (Hydrobiologia, 2014)

Use of Integrated Landscape Indicators to Evaluate the Health of Linked Watersheds and Coral Reef Environments in the Hawaiian Islands - Ku‘ulei S. Rodgers; Michael H. Kido; Paul L. Jokiel; Tim Edmonds; Eric K. Brown (Environmental Management, 2012)

Treatment of Selenium in Simulated Refinery Effluent Using a Pilot-Scale Constructed Wetland Treatment System - Michael M. Spacil; John H. Rodgers; James W. Castle; Cynthia L. Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2011)

A Potential Solution to Mitigate Phosphorus Release Following Clearfelling in Peatland Forest Catchments - Connie O’Driscoll; Michael Rodgers; Mark O’Connor; Zaki-ul-Zaman Asam; Elvira de Eyto; Russell Poole; Liwen Xiao (Water, Air, & Soil Pollution, 2011)

Phenomenological partial-specific volumes for G-quadruplex DNAs - Lance M. Hellman; David W. Rodgers; Michael Gregory Fried (European Biophysics Journal, 2010)

Ruthenium polypyridyl complexes and their modes of interaction with DNA: Is there a correlation between these interactions and the antitumor activity of the compounds? - Eva Corral; Anna C. G. Hotze; Hans den Dulk; Anna Leczkowska; Alison Rodger; Michael J. Hannon; Jan Reedijk (JBIC Journal of Biological Inorganic Chemistry, 2009)

Effect of Aeration Rate on Nutrient Removal from Slaughterhouse Wastewater in Intermittently Aerated Sequencing Batch Reactors - Jianping Li; Mark G. Healy; Xinmin Zhan; Daniel Norton; Michael Rodgers (Water, Air, & Soil Pollution, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Oxygen Transfer and Industrial Wastewater Treatment Efficiency of a Vertically Moving Biofilm System - Michael Rodgers; Xin-Min Zhan; Angela Casey (Water, Air, & Soil Pollution, 2004)

Interaction between a DNA oligonucleotide and a dinuclear iron(II) supramolecular cylinder; an NMR and molecular dynamics study - Erlend Moldrheim; Michael J. Hannon; Isabelle Meistermann; Alison Rodger; Einar Sletten (JBIC Journal of Biological Inorganic Chemistry, 2002)

Insulin-like effects of a physiologic concentration of carnitine on cardiac metabolism - Robert L. Rodgers; Michael E. Christe; George C. Tremblay; John R. Babson; Thomas Daniels (Molecular and Cellular Biochemistry, 2001)

Heavy metal and selenium levels in endangered wood storksMycteria americana from nesting colonies in Florida and Costa Rica - Joanna Burger; James A. Rodgers; Michael Gochfeld (Archives of Environmental Contamination and Toxicology, 1993)